Cultural heritage care and management theory and practice - Salvatore, Cecilia Lizama 1958- (Lanham Rowman & Littlefield, 2018)
"Cultural Heritage Care and Management: Theory and Practice considers all the different components of cultural heritage and provides the tools, technology, and methodology for organizing and arranging, cataloging and describing, exhibiting, providing access, and preserving and conserving these elements"-- Provided by publisher.
Cultural heritage components / Cecilia Lizama Salvatore and John T. Lizama -- Beyond stewardship and consultation : use, care, and protection of indigenous cultural heritage / Loriene Roy and Ciaran Trace -- Ephemerality and permanence : situating performance as intangible cultural heritage / Brian Diettrich -- Cultural heritage and public folklore : tales of tradition / Gregory Hansen -- Legal approaches to the protection of cultural heritage / Patty Gerstenblith -- Roman textiles and heritage in Syria / Tasha Vorderstrasse -- Chamorro language revitalization in the CNMI and Guam / Elizabeth Rechebei and Sandra Chung -- The trilogy of cultural heritage : preserving heritage in an ethnographical museum / Alexandru Chiselev -- Preserving the gastronomical heritage in a multiethnic region : Tulcea County, Dobruja Region, Romania as a case study / Juliana Titov -- The tools and technology in cultural heritage management / Cecilia Lizama Salvatore -- Curating digital cultural heritage materials / Stacy Kowalczyk -- Cultural heritage, audiovisual archives and digital return : the 21st century mandate / Diane Thram -- Toward community engaged archiving : building a digi-rasquache archives / Janet Ceja Alcala and Desiree Alaniz -- The power of lists : world heritage through its information system / Marta Severo -- Tools and methods for georeferencing library heritage / Agata Maggio and Maurizio Lazzari -- Visual environment for cultural heritage (VECH) / Maria Aranzazu Respaldiza and Monica Wachowicz -- Architecture, heritage, and tourism in Nicaragua and Morocco : using cataloging tools to strengthen cultural identities and heritage / Guido Cimadomo - "Memovoice" : approaches to a participative identification of (Ladin) heritage in the Dolomites / Emanuel Valentin.
Includes bibliographical references and index.
Keywords: Archaeology -- Moral and ethical aspects; Cultural property -- Moral and ethical aspects; Cultural property -- Protection; Civilization -- History